Literature Review: Analysis of Moringa Leaf Extract Utilization - Evynurachma, Evynurachma; Dwihendriani, Dwihendriani; Arifahputri, Rosalin (Ridwan Institute, 2023)
Moringa leaves (Moringa oleifera) is one of the natural ingredients that has the potential to be used as an additive in food products, including ice cream. The purpose of this study is to determine the use of Moringa leaf extract from various aspects. This study used the literature review method. Data in this study was collected from various literature sources, such as scientific journals, articles, books, and related research reports. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusions. The results showed that Moringa leaves can be used in various aspects including reducing cholesterol levels, increasing breast milk production, increasing the weight of toddlers and pregnant women, as lactogum and supplements, as antioxidants, preventing malnutrition or stunting, increasing body immunity, alternative food products, affecting the physical stability of pH-related creams, adhesion, dispersion, and viscosity.